The path to clinical implementation of DPYD pharmacogenetic testing: long-term experience from an external quality assessment provider and a university testing center - Hedtke, Maren; Ast, Volker; Leidheiser, Johannes; Kessler, Anja; Neumaier, Michael; Hofheinz, Ralf-Dieter; Haselmann, Verena (Oncology research and treatment, 2025)
Introduction: Pharmacogenetics (PGx) plays a crucial role in precision medicine by identifying genetic variations that influence drug metabolism. For example, variants in dihydropyrimidine dehydrogenase (DPYD) have an impact on DPD enzyme activity and consequently on the metabolization of 5-fluorouracil, which can lead to severe adverse drug reactions. Therefore, pre-emptive DPYD genotyping was endorsed by the European Medicines Agency (EMA) in mid-2020 and subsequently included in national guidelines. In this study, we evaluated the impact of these guidelines on the request behavior for DPYD genotyping at a German university hospital in Mannheim (UMM) and on participation in external quality assessment (EQA) schemes in the European setting. Methods: A retrospective analysis was conducted on 386 DPYD genetic tests performed as part of standard care at the University Medical Center Mannheim from 2015 to 2021. Patient data, including demographics, diagnosis, and treatment, were obtained from electronic health records. Additionally, EQA data from the Reference Institute for Bioanalytics from 2015 to 2023 were analyzed to evaluate the adoption of DPYD testing across European laboratories. Results: The study observed a significant increase in DPYD genotyping requests at UMM following the EMA recommendation in 2020, with an up to 29-fold increase compared to previous years. Furthermore, a shift from post-treatment to pre-treatment genotyping was observed. DPYD variants were detected in 6.5% of cases, with DPYD HapB3 being the most frequent. EQA data from 23,114 genotypes demonstrated a growing participation in proficiency testing across Europe, indicating broader clinical adoption, and confirmed the impact on testing requirements in national guidelines on integration into clinical workflows. Conclusion: The integration of DPYD testing into national guidelines has significantly increased its clinical adoption, enhancing patient safety in oncology. However, standardization challenges remain. Further harmonization of guidelines and expansion of PGx testing may further optimize chemotherapy safety in the future.